Rasionalitas Pengetahuan dan Kemampuan Penanganan Covid-19 (Studi Pemahaman Mahasiswa di Aceh Barat) - Triyanto Triyanto; Rahma Husna Yana; Nurkhalis Nurkhalis; Irma Juraida (Prodi Sosiologi FISIP Universitas Teuku Umar, 2021)
The existence of COVID-19 has attracted the attention of the public, even at the beginning of its appearance, this disease was frightening. However, when there are calls to work at home, worship at home, and various policies that are considered detrimental to the community, and exacerbated by hoax news, slowly there is rejection and even distrust of the existence of COVID-19. So this research was carried out to see how students' knowledge about covid-19 and their belief in the ability of the state through the government both at the center and the regions. Students were chosen as research objects, apart from the fact that some students did not carry out health protocols on campus, also because students were seen as agents of change so that good knowledge of students would bring good knowledge to the community. The results showed that students had good knowledge and were in tune with the information provided by the government. Regarding some students not wearing masks, it was more because they were not in a crowd. Students believe that the state through the government can handle this covid-19 well, although students also see that there are some unsatisfactory things such as the ban on going home, Chinese foreign workers are instead allowed to come. Even though these foreign workers continue to carry out strict screening, they are ensured that they are in safe conditions for the community. The non-applicability of the lockdown is also considered a weakness in handling, even though the government has explained the economic growth that must be fought for.